No association between level of vitamin D and chronic low back pain in Swedish primary care: a cross-sectional case-control study - Andreas Thörneby; Lena Margareta Nordeman; Else Hellebö Johanson (Taylor & Francis Group, 2016)
Objective: Assessment of vitamin D levels and deficiency status in individuals with chronic low back pain (CLBP) in a Swedish general population, compared with controls matched for sex and age. Design: Cross-sectional case-control study. Setting: Primary care, southern Sweden. Subjects: Participants (n = 44) with self-reported low back pain for at least 3 months and individually sex- and age-matched controls without a chronic pain condition (n = 44), recruited from the general population by random letter of invitation. Main outcome measure: Association between vitamin D level and CLBP when adjusting for possible confounders in a multivariate forward conditional logistic regression model. Results: Mean S-25-hydroxyvitamin D levels were 81 and 80 nmol/L in the CLBP and control group, respectively. The prevalence of vitamin D deficiency was low and similar in the CLBP group and the control group. Vitamin D level was not associated with CLBP when potential confounders were taken into account. Conclusions: No difference in vitamin D levels between participants with CLBP and matched controls could be demonstrated in the present sample. Assessment of vitamin D level and deficiency status may be of questionable value in the management of CLBP in primary care settings at similar latitudes, unless there are additional risk factors for deficiency or specific indicators of osteomalacia. Key Points Vitamin D deficiency is common and reported in many chronic pain conditions, including chronic low back pain (CLBP), but evidence for an association and causality is insufficient. The present study found no association between vitamin D levels and CLBP in a case-control sample of 44 + 44 individuals from the Swedish general population. Prevalence of vitamin D deficiency was low and comparable in individuals with CLBP and controls without chronic pain, matched for sex and age. Assessment of vitamin D status, for the purpose of finding and treating an underlying cause of pain, may be of limited value in the management of CLBP in primary care settings at similar latitudes.